2014
DOI: 10.1080/00291951.2014.965740
|View full text |Cite
|
Sign up to set email alerts
|

Women's economic empowerment and formal income: Sri Lankan Export Processing Zones (EPZs) and their impact on gender perceptions of empowerment

Abstract: Women workers in Export Processing Zones (EPZs) in Sri Lanka are often exposed to harsh working conditions and a range of negative social experiences due to their perceived low social status. Research has demonstrated that they experience both empowerment and disempowerment as a result of formal employment. The authors explore the differences between female Sri Lankan EPZ workers who felt empowered (n = 2196) and those who did not (n = 107), and investigate factors that contribute to empowerment. The analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(26 reference statements)
0
7
1
Order By: Relevance
“…The authors are aware that few large-scale quantitative studies have been completed in Sri Lanka and present this paper as an adjunct to the numerous qualitative studies on the topic and research with relatively small sample sizes . As such, this paper presents only quantitative data and compliments several other quantitative analyses published in relation to this research (Hancock, 2014;Hancock et al, 2011a;Hancock et al, 2011b). It should be noted that this paper does not seek to explore concepts of gender, work conditions and empowerment from a theoretical standpoint or develop a conceptual framework, per se.…”
Section: Introductionmentioning
confidence: 56%
“…The authors are aware that few large-scale quantitative studies have been completed in Sri Lanka and present this paper as an adjunct to the numerous qualitative studies on the topic and research with relatively small sample sizes . As such, this paper presents only quantitative data and compliments several other quantitative analyses published in relation to this research (Hancock, 2014;Hancock et al, 2011a;Hancock et al, 2011b). It should be noted that this paper does not seek to explore concepts of gender, work conditions and empowerment from a theoretical standpoint or develop a conceptual framework, per se.…”
Section: Introductionmentioning
confidence: 56%
“…Some studies have found wages to be higher in SEZs (Cirera and Lakshman, 2017), and working conditions to be comparatively favourable (Aggarwal, 2007). SEZs might empower women (Hancock et al, 2014), who in many zones form a large part of the workforce (Tejani, 2011), by bringing them into the labour market. Moreover, SEZs have been used as testing sites for broader economic reforms (UNCTAD, 2019).…”
Section: Benefits and Drawbacks Of Sezsmentioning
confidence: 99%
“…However, the literature from Sri Lanka found that female factory workers have different characteristics in terms of education. Many studies in Sri Lanka found that female factory workers were reasonably well-educated with 10-12 years of school attendance (Attanapola, 2006;Hancock, Carastathis, Georgiou, & Oliveira, 2014). This is in contrast to some Southeast Asian nations such as Cambodia, Laos, Vietnam and Thailand.…”
Section: Working and Living Conditions In The Factoriesmentioning
confidence: 97%
“…Some studies point out that women feel empowered in households or their private sphere, while being victims of capitalism under exploitative working conditions (Mill, 1997;Zaman, 2001;Bélanger & Pendakis, 2010). Also, other studies mention that despite their unpleasant working conditions, women are seen as 'agents of change' and not as victims of globalisation because of their planned strategies and their negotiating roles in both public and private spheres (Hancock et al, 2014;Kabeer, Mahmud & Tasneem, 2011). It is worth noting here that cultural backgrounds of each region might have an effect on the varied results of the research.…”
Section: Factory Work and Empowermentmentioning
confidence: 99%
See 1 more Smart Citation